Norepinephrine or phenylephrine for the prevention of post-spinal hypotension after caesarean section: A double-blinded, randomized, controlled study of fetal heart rate and fetal cardiac output - Sun, Lihong; Tang, Yingying; Guo, Feihe; Liu, Jinping; Xu, Li; Zhu, Guimin; Wang, Yuan; Ma, Na; Chen, XinZhong; Qian, Xiaowei (Journal of clinical anesthesia, 2024)
Spinal anesthesia often causes hypotension, with consequent risk to the fetus. The use of vasopressor agents has been highly recommended for the prevention of spinal anesthesia-induced hypotension during caesarean delivery. Many studies have shown that norepinephrine can provide more stable maternal hemodynamics than phenylephrine. We therefore tested the hypothesis that norepinephrine preserves fetal circulation better than phenylephrine when used to treat maternal hypotension consequent to spinal anesthesia. Prospective, randomized, double-blinded study. Operating room. We recruited 223 parturients with uncomplicated singleton pregnancies who were scheduled for elective caesarean section under combined spinal-epidural anesthesia. The patients received prophylactic intravenous infusion of either 0.08 μg/kg/min norepinephrine or 0.5 μg/kg/min phenylephrine for prevention of spinal anesthesia-induced hypotension. Changes in fetal heart rate and fetal cardiac output before and after spinal anesthesia were measured using noninvasive Doppler ultrasound. 90 subjects who received norepinephrine infusion and 93 subjects who received phenylephrine infusion were ultimately analyzed in the present study. The effects of norepinephrine and phenylephrine on the change of fetal heart rate and fetal cardiac output at 3 and 6 min after spinal block were similar. Although there was a statistically significant decrease in fetal cardiac output at 6 min after subarachnoid block initiation in both the norepinephrine group (mean difference 0.02 L/min; 95% CI, 0–0.04 L/min; P = 0.03) and the phenylephrine group (mean difference 0.02 L/min; 95% CI, 0–0.04 L/min; P = 0.02), it remained within the normal range. Prophylactic infusion of comparable doses of phenylephrine or norepinephrine has similar effects on fetal heart rate and cardiac output changes after spinal anesthesia. Neither phenylephrine nor norepinephrine has meaningful detrimental effects on fetal circulation or neonatal outcomes. •Prophylactic infusion of comparable doses of phenylephrine or norepinephrine has similar effects on fetal heart rate and cardiac output changes after spinal anesthesia.•Neither phenylephrine nor norepinephrine has meaningful detrimental effects on fetal circulation.